Fireproof composition and method for backfilling fireproof compartment penetration

A fireproof composition with specific ratios of organic and inorganic compounds and a water reducing agent addresses brittleness and hardening issues, ensuring stable filling properties during and after heating.

JP7611976B1Active Publication Date: 2025-01-10DENKA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023159231
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-01-10
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

Existing fireproof compositions become brittle and crumble after heating and combustion, losing their filling properties, and they harden over time, making them difficult to process.

Method used

A fireproof composition comprising an organic compound-based binder material, an inorganic compound, and an organic compound-based water reducing agent, with specific mass percentages of each component to maintain processability and shape stability.

Benefits of technology

The composition maintains excellent workability and shape stability after storage and exposure to heat, preventing brittleness and crumbling, ensuring effective filling properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611976000001
    Figure 0007611976000001
  • Figure 0007611976000002
    Figure 0007611976000002
  • Figure 0007611976000003
    Figure 0007611976000003
Patent Text Reader

Abstract

Provided is a fire-resistant composition which has excellent processability, relatively good processability even after storage, and excellent shape stability after heating and combustion. [Solution] According to the present invention, there is provided a fire-resistant composition comprising an organic compound-based binder material, an inorganic compound, and an organic compound-based water-reducing agent, wherein the proportions of each component when the total of the three components, the organic compound-based binder material, the inorganic compound, and the organic compound-based water-reducing agent, is 100 mass%, are 0.5 to 20.0 mass% of the organic compound-based binder material, 60.0 to 98.5 mass% of the inorganic compound, and 0.1 to 20.0 mass% of the organic compound-based water-reducing agent.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a fire-resistant composition and a method for backfilling a fire compartment penetration. [Background technology]

[0002] BACKGROUND ART It is known to provide fireproofing to walls, floors, etc. of buildings by coating or filling them with a fireproof material (fireproof composition). As such a fireproof material, a putty-like fireproof material containing water, an inorganic filler, a thickener, and a binder is used (see Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2021-050118 Summary of the Invention [Problem to be solved by the invention]

[0004] The technology of Patent Document 1 had the problem that even if a plastic film was used for packaging, the water evaporated over time and the fireproof putty material dried out, hardening it and making it difficult to process. Furthermore, the technology of Patent Document 1 has a problem in that the refractory material filled after heating and combustion becomes brittle and easily crumbles, making it difficult to maintain its filling properties.

[0005] The present invention has been made in view of the above circumstances, and provides a refractory composition which has excellent processability, relatively good processability even after storage, and excellent shape stability after heating and combustion. [Means for solving the problem]

[0006] According to the present invention, there is provided a fire-resistant composition comprising an organic compound-based binder material, an inorganic compound, and an organic compound-based water-reducing agent, wherein the proportions of each component when the total of the three components, the organic compound-based binder material, the inorganic compound, and the organic compound-based water-reducing agent, is 100% by mass are 0.5 to 20.0% by mass of the organic compound-based binder material, 60.0 to 98.5% by mass of the inorganic compound, and 0.1 to 20.0% by mass of the organic compound-based water-reducing agent.

[0007] As a result of extensive research, the present inventors have found that a fire-resistant composition containing the components in the above-mentioned proportions can solve the above problems, leading to the completion of the present invention.

[0008] [1] A fire-resistant composition comprising an organic compound-based binder material, an inorganic compound, and an organic compound-based water-reducing agent, wherein the proportions of each component when the total of the three components, i.e., the organic compound-based binder material, the inorganic compound, and the organic compound-based water-reducing agent, is 100% by mass are 0.5 to 20.0% by mass of the organic compound-based binder material, 60.0 to 98.5% by mass of the inorganic compound, and 0.1 to 20.0% by mass of the organic compound-based water-reducing agent. [2] The fire-resistant composition according to [1], wherein the organic compound-based binder material includes a compound containing a sodium salt. [3] The fire-resistant composition according to [1] or [2], wherein the organic compound-based water-reducing agent contains a compound containing a sodium salt. [4] The fire-resistant composition according to any one of [1] to [3], wherein the inorganic compound includes a phosphoric acid-based compound. [5] The fire-resistant composition according to any one of [1] to [4], wherein the organic compound-based binder material contains a compound containing a sodium salt, the inorganic compound contains a phosphate-based compound, and the organic compound-based water-reducing agent contains a compound containing a sodium salt. [6] The fire-resistant composition according to any one of [1] to [5], wherein the fire-resistant composition contains 10 to 70 mass % of water based on 100 mass % of the fire-resistant composition. [7] A method for backfilling a penetration into a fire compartment, comprising a construction step of using the fireproof composition according to any one of [1] to [6]. DETAILED DESCRIPTION OF THE INVENTION

[0009] 1. Composition of the fire-resistant composition The fire-resistant composition of the present invention contains an organic compound-based binder material, an inorganic compound, and an organic compound-based water-reducing agent. The fire-resistant composition of the present invention is a composition that is highly processable and can be used as a putty that can be deformed to fit a desired shape. In other words, the composition can be provided as a putty-like fire-resistant composition.

[0010] <Organic compound binder materials> The organic compound-based binder material is a material that acts as a binding agent to bind together the components of the fire-resistant composition.

[0011] The organic compound binder material is a binding agent made of an organic compound, and by blending an appropriate amount, it is possible to make the fire-resistant composition into a putty-like composition with a hardness suitable for application. The organic compound binder material may be used alone or in combination of two or more. The organic compound binder material preferably includes a compound containing a sodium salt.

[0012] The organic compound binder material is preferably a hydrophilic polymer. Examples of hydrophilic polymers include water-soluble polymers that are soluble in water and water-absorbent polymers that can absorb water and expand, such as starch, cellulose compounds, polyvinyl alcohol, modified acrylic ester copolymers, polyethylene oxide, polypropylene oxide, ethylene oxide-propylene oxide copolymers, ethylene oxide-propylene oxide-phenyl glycidyl ether copolymers, ethylene oxide-propylene oxide-allyl glycidyl ether copolymers, and sodium alginate.

[0013] Examples of the cellulose-based compounds include methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, and derivatives thereof such as salts thereof. Examples of the salts of carboxymethylcellulose include sodium carboxymethylcellulose and ammonium carboxymethylcellulose.

[0014] The modified acrylic acid ester copolymers include a crosslinked product of sulfoethyl acrylate-acrylamide-acrylic acid copolymer sodium salt and a partially crosslinked product of an acrylic acid polymer with sodium salt.

[0015] When the total of the organic compound-based binder material, inorganic compound, and organic compound-based water-reducing agent (hereinafter referred to as "three components") is 100% by mass, the proportion of the organic compound-based binder material is 0.5 to 20.0% by mass, preferably 0.7 to 14.0% by mass, and more preferably 1.1 to 8.0% by mass. If the proportion of the organic compound-based binder material is too small, the fire-resistant composition may be too soft, resulting in insufficient processability or workability. If the proportion of the organic compound-based binder material is too large, the fire-resistant composition may be too hard, resulting in insufficient processability. When the total of the above three components is taken as 100 mass%, the ratio of the organic compound binder material is, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0 mass%, and may be within a range between any two of the numerical values ​​exemplified here.

[0016] <Inorganic compounds> The shape of the inorganic compound may be, for example, spherical, oval, cubic, rectangular, or random, and may be hollow or solid. The average particle size of the particulate inorganic compound is, for example, 10 to 1000 μm, preferably 20 to 800 μm, more preferably 30 to 500 μm, and even more preferably 40 to 200 μm. The "average particle size" refers to the particle size at 50% of the cumulative value in the particle size distribution determined by a laser diffraction / scattering method. These may be used alone or in combination of two or more.

[0017] Examples of inorganic compounds include metal oxides such as alumina, silica, aluminosilicate, zinc oxide, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, and ferrites; hydrated inorganic substances such as calcium hydroxide, magnesium hydroxide, aluminum hydroxide, and hydrotalcite; metal carbonates such as basic magnesium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate, strontium carbonate, and barium carbonate; calcium salts such as calcium sulfate and calcium silicate; glass beads, silica-based balloons, aluminum nitride, boron nitride, silicon nitride, carbon black, graphite, carbon balloons, charcoal powder, various metal powders, potassium titanate, magnesium sulfate, lead zirconate titanate, aluminum borate, molybdenum sulfide, silicon carbide, zinc borate, various magnetic powders, fly ash, inorganic hollow fillers, perlite, obsidian, perlite, colophonite, diatomaceous earth, dehydrated sludge, boron, sodium tetraborate hydrate (borax), and phosphate compounds. These may be used alone or in combination of two or more. From the viewpoint of shape stability after combustion, the inorganic compound preferably contains aluminum hydroxide or a phosphate compound, and more preferably contains aluminum hydroxide and a phosphate compound.

[0018] <Phosphate compounds> In addition to phosphoric acid compounds, phosphorous acid compounds include phosphorous acid compounds, hypophosphorous acid compounds, metaphosphate compounds, pyrophosphate compounds, and polyphosphate compounds.

[0019] Examples of phosphate compounds include monoaluminum phosphate, monosodium phosphate, monopotassium phosphate, monocalcium phosphate, monozinc phosphate, dialuminum phosphate, disodium phosphate, dipotassium phosphate, dicalcium phosphate, dizinc phosphate, trialuminum phosphate, trisodium phosphate, tripotassium phosphate, tricalcium phosphate, trizinc phosphate, trimagnesium phosphate, monoammonium phosphate, diammonium phosphate, tricalcium phosphate, and aluminum phosphate.

[0020] Examples of the phosphite compounds include aluminum phosphite, aluminum hydrogen phosphite, sodium phosphite, potassium phosphite, calcium phosphite, and zinc phosphite.

[0021] Examples of hypophosphite compounds include aluminum hypophosphite, sodium hypophosphite, potassium hypophosphite, calcium hypophosphite, and zinc hypophosphite.

[0022] Examples of metaphosphate compounds include aluminum metaphosphate, sodium metaphosphate, potassium metaphosphate, calcium metaphosphate, zinc metaphosphate, and sodium hexametaphosphate.

[0023] An example of the pyrophosphate compound is sodium pyrophosphate.

[0024] Examples of polyphosphate compounds include ammonium polyphosphate and melamine-modified ammonium polyphosphate.

[0025] When the total of the above three components is taken as 100% by mass, the proportion of the inorganic compound is 60.0 to 98.5% by mass, preferably 84.5 to 98.3% by mass, and more preferably 90.5 to 97.9% by mass. If the proportion of the inorganic compound is too low, shape stability after heating and combustion may be insufficient. If the proportion of the inorganic compound is too high, processability may be poor. Specific examples of the proportion of the inorganic compound when the total of the above three components is taken as 100% by mass include: 60.0, 61.0, 62.0, 63.0, 64.0, 65.0, 66.0, 67.0, 68.0, 69.0, 70.0, 71.0, 72.0, 73.0, 74.0, 75.0, 76.0, 77.0, 78.0, 79.0, and 80%. 0, 81.0, 82.0, 83.0, 84.0, 84.5, 85.0, 86.0, 87.0, 88.0, 89.0, 90.0, 90.5, 91.0, 92.0, 93.0, 94.0, 95.0, 96.0, 97.0, 97.9, 98.0, 98.3, 98.5 mass%, and may be within a range between any two of the numerical values ​​exemplified herein.

[0026] From the viewpoint of shape stability after heating and combustion, aluminum hydrogen phosphite, ammonium polyphosphate, etc. are preferred as the phosphoric acid compound.

[0027] <Organic compound water reducing agent> Organic compound-based water-reducing agents are compounds made of organic compounds and are dispersants that have the effect of dispersing other components. The dispersing effect is achieved, for example, by static electricity repulsion. Examples of organic compound-based water-reducing agents include lignin-based compounds, naphthalenesulfonic acid-based compounds, aminosulfonic acid-based compounds, polycarboxylic acid-based compounds, and polyether-based compounds. These may be used alone or in combination of two or more.

[0028] Examples of lignin compounds include metal salts of lignin sulfonate such as magnesium salt of lignin sulfonate, sodium salt of lignin sulfonate, and calcium salt of lignin sulfonate, and modified products thereof.

[0029] Examples of naphthalenesulfonic acid compounds include sodium naphthalenesulfonic acid formalin condensate, sodium naphthalenesulfonic acid-formaldehyde condensate, and the like.

[0030] Examples of polyether compounds include carboxyl group-containing polyether compounds such as methacrylic acid-methacrylic acid ethylene oxide ester copolymer salts.

[0031] When the total of the above three components is taken as 100% by mass, the proportion of the organic compound-based water-reducing agent is 0.1 to 20.0% by mass, preferably 0.3 to 14.0% by mass, and more preferably 0.7 to 8.0% by mass. If the proportion of the organic compound-based water-reducing agent is too low, workability after storage may be insufficient. If the proportion of the organic compound-based water-reducing agent is too high, workability, workability, and post-drying strength may be impaired. When the total of the above three components is taken as 100% by mass, the proportion of the organic compound-based water-reducing agent is, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, and 9. 0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0 mass%, and may be within a range between any two of the numerical values ​​exemplified here.

[0032] The organic water-reducing agent preferably contains a compound containing a sodium salt, such as sodium lignin sulfonate, sodium naphthalenesulfonate-formaldehyde condensate, or sodium naphthalenesulfonate-formaldehyde condensate, which have a sodium salt in their skeleton.

[0033] In addition, additives such as thermally expandable compounds, fibrous compounds, AE (Air Entraining) agents, preservatives, mildew inhibitors, antioxidants, softeners, and tackifiers may be added to the fire-resistant composition as appropriate, provided that the physical properties are not impaired.

[0034] <Thermally expandable compound> The thermally expandable compound is not particularly limited as long as it expands when heated, and examples thereof include microspheres, melamine, azo compounds, nitroso compounds, hydrazine derivatives, bicarbonates, vermiculite, kaolin, mica, thermally expandable graphite, etc. Among these, it is preferable to include thermally expandable graphite from the viewpoint of thermal expandability.

[0035] <Thermal Expandable Graphite> Thermally expandable graphite is a crystalline compound that is obtained by surface-treating graphite powder, such as natural graphite or pyrolytic graphite, with an inorganic acid, such as sulfuric acid or nitric acid, and a strong oxidizing agent, such as concentrated nitric acid or permanganate, and that maintains a graphite layer structure. When exposed to a temperature equal to or higher than the expansion initiation temperature (approximately 200°C) under normal pressure, it thermally expands by 100 times or more. Note that the graphite powder, such as natural graphite or pyrolytic graphite, may be subjected to a deoxidation treatment or further neutralization treatment.

[0036] The proportion of the thermally expandable graphite is preferably 0.3 to 30.0 parts by mass when the total of the above three components is 100 parts by mass. This range makes it possible to achieve both thermal expandability and shape stability after thermal expansion.

[0037] <Fibrous compounds> Fibrous compounds include inorganic fibrous compounds and organic fibrous compounds, and may contain both inorganic fibrous compounds and organic fibrous compounds. The fibrous compound only needs to have a fibrous shape. Examples of the cross-sectional shape of the fibrous compound include circular, elliptical, polygonal, etc. The ratio L / D of the length L to the diameter D of the fibrous compound is, for example, greater than 10, preferably 50 or more, and more preferably 100 or more. The upper limit of L / D is not particularly defined, but is, for example, 10000. The diameter D of the fibrous compound is, for example, 1 to 100 μm, preferably 2 to 50 μm, and more preferably 5 to 20 μm. The length L of the fibrous compound is, for example, 0.05 to 10 mm, preferably 0.1 to 8 mm, and more preferably 0.2 to 5 mm.

[0038] Examples of the inorganic fibrous compound include glass fiber (E glass fiber, C glass fiber, S glass fiber, D glass fiber), rock wool, ceramic fiber (silica alumina fiber, alumina fiber, silica fiber), zirconia fiber, carbon fiber, bulk alkali earth silicate fiber, gypsum fiber, carbon fiber, metal fiber, slag fiber, basalt fiber, etc.

[0039] Examples of the organic fibrous compound include meta-aramid fiber, para-aramid fiber, amide fiber, pulp fiber, cellulose fiber, polyparaphenylene benzobisoxazole fiber, polyarylate fiber, etc.

[0040] <AE agent> Examples of the AE agent include anionic surfactants, nonionic surfactants, resin acid salt surfactants, etc. These may be used alone or in combination of two or more.

[0041] The fire-resistant composition of the present invention preferably contains water to facilitate sealing of gaps between pipes and cables and fire walls in buildings. When the fire-resistant composition contains water, the solid content is preferably 30 to 90 mass %, more preferably 50 to 70 mass %. The fire-resistant composition contains preferably 10 to 70 mass %, more preferably 30 to 50 mass %, of water per 100 mass % of the fire-resistant composition. If the water content is low (the solid content is high), the putty may become crumbly and may be difficult to process. If the water content is high (the solid content is low), the putty may be too soft and difficult to process and work. Specific examples of the water content are 10, 15, 20, 25, 26, 30, 35, 40, 45, 50, 55, 60, 65, and 70% by mass, and may be within a range between any two of the values ​​exemplified here.

[0042] The fire-resistant composition of the present invention can be used as a joint material to seal gaps between pipes and cables and fire walls in buildings.

[0043] 2.Method for producing refractory composition The fire-resistant composition of the present invention can be produced by mixing and stirring the above three components, optional additives, and water using a mixer or the like.

[0044] 3. Backfilling method for fire compartment penetrations A method for backfilling a penetration into a fire compartment according to another aspect of the present invention is a method including a construction step using the above-mentioned fireproof composition.

[0045] In the construction process, for example, the fireproof composition is filled into gaps between a fire wall or the like serving as a fire compartment through which pipes and cables pass in a building and the pipes and cables themselves. [Example]

[0046] 1. Preparation of Refractory Composition The components shown in Tables 1 to 4 were mixed and stirred using a mixer according to the compositions (units: mass%) in the tables to prepare putty-like fire-resistant compositions for Examples and Comparative Examples. Note that in the tables, the blending amounts of the binder material, inorganic compound, water-reducing agent, and medium relative to a total of 100 mass% (total composition) are shown for the combined total of the three components of binder material, inorganic compound, and water-reducing agent, and for the medium, and further the blending amounts of each of the binder material, inorganic compound, and water-reducing agent relative to a total of 100 mass% of the above three components are shown.

[0047] [Table 1] [Table 2] [Table 3] [Table 4]

[0048] Details of the components in the table are as follows: <Organic compound binder materials> Sodium carboxymethylcellulose: "Sodium carboxymethylcellulose" manufactured by Hayashi Pure Chemical Industries, Ltd. Ammonium carboxymethylcellulose: "Kiccolate NA-H" manufactured by Nichirin Chemical Industry Co., Ltd. Acrylic acid polymer partial sodium salt: Fujifilm Wako Pure Chemical Industries, Ltd. "Superabsorbent polymer (acrylate salt type)" Methylcellulose: Shin-Etsu Chemical Co., Ltd. "MCE-4000" <Inorganic compound binder materials> Bentonite: "Akagi" manufactured by Hojun Co., Ltd.

[0049] <Inorganic compounds> Aluminum hydroxide: "C-301N" manufactured by Sumitomo Chemical Co., Ltd. Aluminum hydrogen phosphite: "NSF" manufactured by Taihei Chemical Industry Co., Ltd. Ammonium polyphosphate: HP-APP II, manufactured by SCM Industrial Chemical Co., Ltd.

[0050] <Organic compound water reducing agent> Lignosulfonic acid sodium salt: "Pearlex NP" manufactured by Nippon Paper Industries Co., Ltd. Lignosulfonic acid magnesium salt: "Sunex P321" manufactured by Nippon Paper Industries Co., Ltd. Naphthalenesulfonic acid formalin condensate sodium: "Mighty HS" manufactured by Kao Corporation Naphthalenesulfonic acid-formaldehyde condensate sodium salt: "Mighty 150" manufactured by Kao Corporation Carboxyl group-containing polyether compound: Kao Corporation's "Mighty 1000M" <Inorganic compound water reducing agent> Sodium tripolyphosphate: Yoneyama Chemical Industry Co., Ltd.

[0051] <Various evaluations> The fire-resistant compositions of the Examples and Comparative Examples were subjected to the following evaluations, and the results are shown in Tables 1 to 4.

[0052] <Workability> The fire-resistant compositions of the Examples and Comparative Examples before drying (before storage over time, as described below) were measured for softness (softness A) in accordance with JIS A5752 at a load of 150 g and a temperature of 21°C. A specified cone was inserted vertically into the test piece, and the penetration depth was measured to the nearest 0.1 mm. Then, the workability was evaluated based on the penetration depth using the following evaluation criteria. [Evaluation criteria] ◎: The penetration depth is 180 [1 / 10 mm] or more and less than 220 [1 / 10 mm]. ○: Penetration depth is 150 [1 / 10 mm] or more and less than 180 [1 / 10 mm], Or, it is 220 [1 / 10 mm] or more and less than 250 [1 / 10 mm]. △: Penetration depth is 110 [1 / 10 mm] or more and less than 150 [1 / 10 mm], Or, it is 250 [1 / 10 mm] or more and less than 280 [1 / 10 mm]. ×: The penetration depth is less than 110 [1 / 10 mm] or 280 [1 / 10 mm] or more.

[0053] <Processability after storage (processability over time)> The fire-resistant compositions (before storage) of the Examples and Comparative Examples before drying were placed in 80 μm-thick polyethylene bags, sealed, and stored at 40°C for 90 days to obtain fire-resistant compositions (after storage). The fire-resistant compositions (after storage) thus obtained were subjected to softness measurement (softness B) in accordance with JIS A5752 at a load of 150 g and a temperature of 21°C. A specified cone was inserted vertically into the test piece, and the penetration depth was measured to the nearest 0.1 mm. Then, based on the penetration depth, the processability after storage was evaluated according to the following evaluation criteria. [Evaluation criteria] ◎: The penetration depth is 150 [1 / 10 mm] or more. ○: The penetration depth is 130 [1 / 10 mm] or more and less than 150 [1 / 10 mm]. △: The penetration depth is 90 [1 / 10 mm] or more and less than 130 [1 / 10 mm]. ×: The penetration depth is less than 90 [1 / 10 mm] or 280 [1 / 10 mm] or more.

[0054] <Softness change rate> The change rate of softness is the rate of change of softness before and after storage, and is a value calculated based on the following formula. Softness change rate (%) = 100 x (softness A - softness B) / softness A [Evaluation criteria] ◎: Less than 25%. ○: 25% or more and less than 30%. △: 30% or more and less than 50%. ×: 50% or more.

[0055] <Workability (non-sticking to gloves)> Wearing latex rubber gloves, participants gripped 100 g of the undried fire-resistant compositions of the Examples and Comparative Examples (before storage over time) 10 times, and then measured the weight of the residue on the gloves. The weight of the residue was calculated using the following formula. Based on the weight of the residue, the non-stickiness of the gloves was evaluated according to the following criteria. Weight of the deposit [g] = (weight of the glove after squeezing the fire-resistant composition 10 times) - (weight of the original glove) [Evaluation criteria] ⊚: The weight of the deposit is less than 0.1 g. ○: The weight of the deposit is 0.1 [g] or more and less than 0.4 [g]. △: The weight of the deposit is 0.4 [g] or more and less than 0.7 [g]. ×: The weight of the deposit is 0.7 g or more.

[0056] <Strength after drying> Using the fire-resistant compositions of the Examples and Comparative Examples before drying (before the aforementioned storage), test pieces measuring 30 mm long x 30 mm wide x 4 mm thick were prepared, and these were dried at 110°C for 24 hours to obtain test pieces of the fire-resistant compositions after drying. The test pieces were subjected to a three-point bending test using a jig (upper pushing side tip R1 mm and width 80 mm, lower two-point support side R1 mm, width 80 mm, support distance 20 mm) at a compression rate of 50 mm / min to measure their strength (three-point bending fracture strength). Here, a higher three-point bending fracture strength indicates higher shape stability after drying. Based on the three-point bending fracture strength, the shape stability after drying was evaluated according to the following criteria. [Evaluation criteria] ⊚: The three-point bending breaking strength is 60 [N] or more. ◯: The three-point bending breaking strength is 50 [N] or more and less than 60 [N]. △: The three-point bending breaking strength is 40 [N] or more and less than 50 [N]. ×: The three-point bending breaking strength is less than 40 [N].

[0057] <Shape stability after heating and combustion> Using the undried fire-resistant compositions of the Examples and Comparative Examples (before the aforementioned storage), test pieces measuring 30 mm long x 30 mm wide x 4 mm thick were prepared. These were then dried at 110°C for 24 hours to obtain test pieces of the dried fire-resistant compositions. The dried test pieces were then left in an atmosphere maintained at 300°C for 0.5 hours, and then the strength (three-point bending fracture strength) of the test pieces was measured at a compression rate of 50 mm / min using a three-point bending test jig (upper push side tip R1 mm and width 80 mm, lower two-point support side R1 mm, width 80 mm, support distance 20 mm). Here, a higher three-point bending fracture strength indicates a higher strength after thermal combustion. Based on the three-point bending fracture strength, the shape stability after thermal combustion was evaluated according to the following evaluation criteria. [Evaluation criteria] ⊚: The three-point bending breaking strength is 2.0 [N] or more. ◯: The three-point bending breaking strength is 1.5 [N] or more and less than 2.0 [N]. △: The three-point bending breaking strength is 1.0 [N] or more and less than 1.5 [N]. ×: The three-point bending breaking strength is less than 1.0 [N].

Claims

1. An organic compound-based binder material; An inorganic compound; An organic compound-based water reducing agent, The ratio of each component when the total of the three components, the organic compound-based binder material, the inorganic compound, and the organic compound-based water reducing agent, is 100 mass %: 3.0 to 20.0% by mass of the organic compound-based binder material, 60.0 to 90.5% by mass of the inorganic compound, 2.0 to 20.0% by mass of the organic compound-based water reducing agent, The fire-resistant composition according to claim 1,

2. The fire-resistant composition of claim 1 , wherein the organic compound-based binder material comprises a compound containing a sodium salt.

3. The fire-resistant composition according to claim 1 or 2, wherein the organic compound-based water-reducing agent comprises a compound containing a sodium salt.

4. The fire-resistant composition according to claim 1 or 2, wherein the inorganic compound comprises a phosphoric acid-based compound.

5. the organic compound-based binder material includes a compound containing a sodium salt, The inorganic compound includes a phosphoric acid compound, The fire resistant composition of claim 1 , wherein the organic compound-based water reducer comprises a compound containing a sodium salt.

6. The fire-resistant composition according to claim 1 or claim 2, wherein the fire-resistant composition contains 10 to 70 mass% of water in 100 mass% of the fire-resistant composition.

7. A method for backfilling a fire compartment penetration, comprising a step of applying the fireproof composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Refraction composition

    JP2001058878A

  • Alumina cement composition, and monolithic refractory obtained by using the composition

    JP2003119067A

  • Silicon carbide material for monolithic refractory excellent in driability and monolithic refractory material

    JP2003321276A

  • Carbon-containing castable refractory and method for producing carbon-containing castable refractory

    JP2018184315A

  • Refractory material, refractory material stored in container, and construction method of refractory material

    JP2021050118A